2017
DOI: 10.1109/te.2016.2562611
|View full text |Cite
|
Sign up to set email alerts
|

After the Workshop: A Case Study of Post-Workshop Implementation of Active Learning in an Electrical Engineering Course

Abstract: Engineering education research has empirically validated the effectiveness of active learning over traditional instructional methods. However, the dissemination of education research into instructional practice has been slow. Faculty workshops for current and future instructors offer a solution to promote the widespread adoption of active learning in engineering classrooms. However, most of the existing research has relied on faculty selfreporting to evaluate the success of engineering faculty workshops. Resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 42 publications
(59 reference statements)
1
15
0
Order By: Relevance
“…The results are in line with previous research on how instructors' decisions to engage in effective implementation of research‐based instructional practices relies heavily on their instructional and personal preferences (Henderson et al ). These results also highlight the importance of faculty development efforts in promoting sound pedagogical practices and learning theories in order to support effective adoption of innovations, as was recently suggested by Shekhar and Borrego ().…”
Section: Summary Concluding Remarks and Recommendationssupporting
confidence: 77%
See 2 more Smart Citations
“…The results are in line with previous research on how instructors' decisions to engage in effective implementation of research‐based instructional practices relies heavily on their instructional and personal preferences (Henderson et al ). These results also highlight the importance of faculty development efforts in promoting sound pedagogical practices and learning theories in order to support effective adoption of innovations, as was recently suggested by Shekhar and Borrego ().…”
Section: Summary Concluding Remarks and Recommendationssupporting
confidence: 77%
“…While these factors apply across the general field of engineering education, there is a need to identify discipline‐specific factors that may hinder or facilitate adoption of innovations. As suggested by Borrego et al (), the value of a certain innovation varies according to the specific engineering discipline, simply due to the specific technical skills and educational content pertaining to the discipline. This is also supported by earlier studies on behavioral prediction and behavior change (e.g., Theory of Planned Behavior, Ajzen 2018) that link an individual's behavioral intentions and actual behaviors to subjective norms and perceived behavioral control.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, using [12]- [15], and based on the selected competences, the DT and the INCan defined the challenge as "design and implement computer applications to support the follow-up of patients with breast cancer before and during their treatment". Because of the technology that we planned to use, the i-Sem was registered under the title of "Data Analytic and Cloud Computing vs Breast Cancer: Learning that Helps".…”
Section: The Origin Of the Daandccvsbc Projectmentioning
confidence: 99%
“…Active learning is defined as in-class work by students that goes beyond simply listening to the instructor and taking notes [6]. Despite the known benefits of active learning, lecture-based teaching in STEM is still the prevalent approach, with active learning in general propagating at a slow rate [5], [7], [8]. For example, in electrical and computer engineering (ECE) departments, where the courses in the present paper are housed, a survey of U.S. faculty indicated that only 30% at the time were utilizing the very accessible and simple think-pair-share (TPS) technique that drives analysis and interactivity, with 54% of ECE faculty members having abandoned use of the technique after trying it [9].…”
Section: Introduction: Literature Review and Instructor Backgroundmentioning
confidence: 99%